Assessment of Ex Vivo Transport Function in Isolated Rodent Brain Capillaries. Issue 1 (17th March 2017) - Chan, Gary N.Y.; Cannon, Ronald E.
Abstract: The blood‐brain barrier plays an important role in neuroprotection; however, it can be a major obstacle for drug delivery to the brain. This barrier primarily resides in the brain capillaries and functions as an interface between the brain and peripheral blood circulation. Several anatomical and biochemical elements of the blood‐brain barrier are essential to regulate the permeability of nutrients, ions, hormones, toxic metabolites, and xenobiotics into and out of the brain. In particular, high expression of ATP‐driven efflux transporters at the blood‐brain barrier is a major obstacle in the delivery of CNS pharmacotherapeutics to the brain. The complete understanding of these elements can offer insights on how to modulate barrier functions for neuroprotection against CNS drug toxicity and to enhance drug delivery to the brain. In the literature, preclinical models of the blood‐brain barrier are widely utilized to predict drug pharmacokinetics and pharmacodynamics properties in the brain. In addition, these models are essential tools to investigate cellular mechanisms and novel interventions that alter barrier function and permeability. This unit presents procedures to isolate fresh and viable rodent brain capillaries for the assessment of ex vivo transport activity at the blood‐brain barrier. © 2017 by John Wiley & Sons, Inc.